2019
DOI: 10.1155/2019/4569614
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation Suppresses Sleep Deprivation-Induced Telomere Dysfunction and Senescence-Associated Secretory Phenotype (SASP)

Abstract: Sleep deprivation is reported to cause oxidative stress and is hypothesized to induce subsequent aging-related diseases including chronic inflammation, Alzheimer’s disease, and cardiovascular disease. However, how sleep deprivation contributes to the pathogenesis of sleep deficiency disorder remains incompletely defined. Accordingly, more effective treatment methods for sleep deficiency disorder are needed. Thus, to better understand the detailed mechanism of sleep deficiency disorder, a sleep deprivation mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…Recent studies demonstrated that folic acid plays an important role in preventing diseases related to oxidative stress [60]. A previous study indicated that folic acid supplementation improved sleep deficiencyrelated disorders improving oxidative stress [61]. In line with our findings, the study by Baldwin et al reported reduced dietary intake of folic acid, and vitamins C and E for subjects diagnosed with OSA compared to subjects without OSA [62].…”
Section: Plos Onesupporting
confidence: 91%
“…Recent studies demonstrated that folic acid plays an important role in preventing diseases related to oxidative stress [60]. A previous study indicated that folic acid supplementation improved sleep deficiencyrelated disorders improving oxidative stress [61]. In line with our findings, the study by Baldwin et al reported reduced dietary intake of folic acid, and vitamins C and E for subjects diagnosed with OSA compared to subjects without OSA [62].…”
Section: Plos Onesupporting
confidence: 91%
“…Xu et al reported miRNA-361 directly targeted Hsp90 to suppress its expression, leading to higher survival rate in cervical cancer patients (Xu et al 2020 ). Hu et al used Hsp90 inhibitor SNX2112 to treat human cervical cancer cells, and caused TRAIL-induced apoptosis of human cervical cancer cells (Hu et al 2019 ). In our study, we investigated the Hsp90 expression in clinical samples, and confirmed high Hsp90 expression in HPV16 + cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate AE decreases oxidative stress and inflammation, but excessive exercise increases the level of oxidative stress in the body (29). Studies have shown that long-term oxidative stress induces a high-load state in the heart and blood vessels and causes cardiovascular disease, including atherosclerosis, heart failure and myocardial fibrosis (30)(31)(32). Therefore, decreasing oxidative stress and inflammation is key to preventing cardiovascular system injury.…”
Section: Discussionmentioning
confidence: 99%